Hubungan Gangguan Sistem Kardiovaskuler pada Kehamilan dengan Kejadian Berat Badan Lahir Di RSUD Arjawinangun - Kasmad Kasmad; Ani Nurhaeni; Dewi Erna Marisa (Publikasi Indonesia, 2022)
Changes in the function of the cardiovascular system in pregnant women are characterized by an increase in blood volume, cardiac output, heart rate, stroke volume, and decreased vascular resistance. Preeclampsia and hypertension contribute greatly to 10-15% of the total deaths of pregnant women in the world. Preeclampsia and hypertension in pregnant women is the biggest risk factor for low birth weight babies (LBW) because it can cause reduced blood flow to the placenta and fetal growth is stunted. The purpose of this study was to determine the relationship of cardiovascular system disorders in pregnancy with birth weight events. The method in this study uses the correlation description method with a retrospective approach. The population in this study were mothers who gave birth with cardiovascular system disorders in the delivery room of Arjawinangun Regional Hospital. The population in this study was 172 people in the period January - March 2019. The size of the sample to be studied as many as 47 people were taken by simple random sampling. Bivariate data analysis uses the chi-square correlation test. The instrument uses a questionnaire. The results showed that most respondents (63.8%) had hypertension and cardiovascular disorders and most respondents (63.8%) had normal birth weight. The conclusion of this study there is a relationship between cardiovascular system disorders and birth weight in Dewi Sartika Arjawinangun Regional Hospital p value = 0,000; ? <0.05.